2012
DOI: 10.1111/j.1476-5381.2012.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na+‐H+ exchange as a mechanism of rapid cardioprotection by resveratrol

Abstract: BACKGROUND AND PURPOSEResveratrol is a polyphenol abundantly found in grape skin and red wine. In the present study, we investigated whether resveratrol exerts protective effects against cardiac ischaemia/reperfusion and also explored its mechanisms. EXPERIMENTAL APPROACHInfarct size and functional recovery in rat isolated perfused hearts subjected to no-flow global ischaemia followed by reperfusion were measured. Cultured neonatal rat cardiomyocytes were exposed to H2O2 (100 mmol·L -1 ) to induce cell injury.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
1
17
0
3
Order By: Relevance
“…In fact, previous studies revealed that NCX inhibitors such as KB‐R7943 and SEA0400 exerted cardioprotective effects against ischaemia/reperfusion injury by attenuating [Ca 2+ ] i overload . Consistently, we previously demonstrated that resveratrol exerted cardioprotection by suppressing NCX‐mediated increase in [Ca 2+ ] i level induced by H 2 O 2 . As mentioned above, hyponatraemia may activate the reverse mode of the NCX and increases [Ca 2+ ] i concentration, which leads to phosphorylation of CaMKII and increase in ROS levels .…”
Section: Discussionsupporting
confidence: 80%
“…In fact, previous studies revealed that NCX inhibitors such as KB‐R7943 and SEA0400 exerted cardioprotective effects against ischaemia/reperfusion injury by attenuating [Ca 2+ ] i overload . Consistently, we previously demonstrated that resveratrol exerted cardioprotection by suppressing NCX‐mediated increase in [Ca 2+ ] i level induced by H 2 O 2 . As mentioned above, hyponatraemia may activate the reverse mode of the NCX and increases [Ca 2+ ] i concentration, which leads to phosphorylation of CaMKII and increase in ROS levels .…”
Section: Discussionsupporting
confidence: 80%
“…A recently identified target of resveratrol is the Na C /H C exchanger type 1 (NHE1) (46). Interestingly, NHE1 activity was shown earlier to be increased by VGSC activity in breast cancer cells and the resulting pericellular acidification contributed to extracellular proteolysis and invasiveness (47).…”
Section: Effects Of Resveratrol On Cell Behaviorsmentioning
confidence: 98%
“…Ca 2+ overload can be induced by the depression of SR Ca 2+ recycling and enhancement of diastolic SR Ca 2+ leak. Furthermore, it can be induced by intracellular acidosis (pH i ) through the activation of the sarcolemmal Na + –H + exchanger (NHE) to extrude H + driven by the transmembrane Na + gradient in cardiomyocytes . Increases in the intracellular concentration of Na + ([Na + ] i ) induced by increased Na + –H + exchange facilitate Ca 2+ influx through the NCX working in reverse mode.…”
Section: Modulation Of Calcium Signaling In the Heartmentioning
confidence: 99%
“…Furthermore, intracellular Ca 2+ overload leads to mitochondrial Ca 2+ overload, which induces mitochondrial permeability transition pore opening and consequent apoptosis . A series of studies has indicated that Res prevents intracellular Ca 2+ overload by inhibiting the activation of NHE . Recently, the newly developed Res analog HS‐1793 (4‐(6‐hydroxy‐2‐naphthyl)‐1,3‐benzenediol, 10 μM) was shown to prevent mitochondrial Ca 2+ overload and attenuate mitochondrial damage .…”
Section: Modulation Of Calcium Signaling In the Heartmentioning
confidence: 99%